2006
DOI: 10.1162/jocn.2006.18.11.1850
|View full text |Cite
|
Sign up to set email alerts
|

Visual Grouping and the Focusing of Attention Induce Gamma-band Oscillations at Different Frequencies in Human Magnetoencephalogram Signals

Abstract: Neural oscillatory synchrony could implement grouping processes, act as an attentional filter, or foster the storage of information in short-term memory. Do these findings indicate that oscillatory synchrony is an unspecific epiphenomenon occurring in any demanding task, or that oscillatory synchrony is a fundamental mechanism involved whenever neural cooperation is requested? If the latter hypothesis is true, then oscillatory synchrony should be specific, with distinct visual processes eliciting different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
143
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(162 citation statements)
references
References 73 publications
17
143
1
1
Order By: Relevance
“…Therefore, the faint stimuli used here induced a weak yet reliable gamma-band response over the visual cortex. Similar parieto-occipital increases of gamma-band activity have been observed previously in the scalp MEG using visual stimuli at maximal contrast (Hoogenboom et al, 2006;Vidal et al, 2006;Siegel et al, 2007).…”
Section: Identification Of the Gamma-band Response To The Faint Stimulisupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, the faint stimuli used here induced a weak yet reliable gamma-band response over the visual cortex. Similar parieto-occipital increases of gamma-band activity have been observed previously in the scalp MEG using visual stimuli at maximal contrast (Hoogenboom et al, 2006;Vidal et al, 2006;Siegel et al, 2007).…”
Section: Identification Of the Gamma-band Response To The Faint Stimulisupporting
confidence: 87%
“…Our results thus confirm the involvement of gamma-band activity in both visual awareness and spatial attention. However, the results further show that distinct frequency components of the gamma-band response may support flexibly and simultaneously distinct cognitive functions (Vidal et al, 2006;Buschman and Miller, 2007). Such a frequency specialization suggests that gamma-band synchronization is not a monolithic mechanism in charge of a single cognitive function (Tallon-Baudry, 2004;Tallon-Baudry et al, 2005;Buzsaki, 2006).…”
Section: Visual Awareness and Spatial Attention Have Different Time Cmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous reports on stimulus-locked spectral responses often used rather simple stimulus configurations like geometrical shapes (Busch et al 2004;Fründ et al 2007b) or gratings (Bodis-Wollner et al 2001;Busch et al 2006b;Fründ et al 2007a;Schadow et al 2007) and observed response frequencies between 30 and \90 Hz. Other studies that applied more complex stimuli (Busch et al 2006a;Gruber and Müller 2005;Lachaux et al 2005;Tallon-Baudry et al 1997;Vidal et al 2006) either did not observe stimulus-locked c responses at all, or did not find these responses to be modulated by experimental manipulations. Our results are in line with these findings in that we did not find any stimulus-locked c responses at all.…”
Section: Spectral Responses At High Frequenciesmentioning
confidence: 88%
“…Grouping may be mediated by synchronization of activity between neurons representing different elements of a group. Although some neurophysiological recordings in animals (e.g., Castelo-Branco, Goebel, Neuenschwander, & Singer, 2000;Singer & Gray, 1995) and EEG recordings in humans (e.g., Tallon- -Baudry, 2006) have supported this idea, it remains a controversial hypothesis (e.g., Lamme & Spekreijse, 1998;Roelfsema, Lamme, & Spekreijse, 2004). Much of that evidence applies to limited types of grouping such as collinearity/continuity (e.g., Singer & Gray, 1995) or formation of illusory contours based on these features (e.g., Tallon-Baudry & Bertrand, 1999).…”
Section: Mechanisms Of Groupingmentioning
confidence: 99%